2011
DOI: 10.1017/s1742758411000397
|View full text |Cite
|
Sign up to set email alerts
|

Bemisia tabaci (Hemiptera: Aleyrodidae) on Leucaena leucocephala (Fabaceae): a new host record from India and a comparative study with a population from cotton

Abstract: Biology, morphometrics and analyses of non-specific esterases were carried out for populations of Bemisia tabaci (Gennadius) collected from leucaena [Leucaena leucocephala (Lam.) de Wit] in New Delhi, India and compared with those for cotton populations. The developmental periods of the egg, and the first to fourth instars of the leucaena populations were 6.7^0.18, 4.2^0.18, 3.8^0.14, 3.0^0.0 and 5.2^0.18 days, respectively, with a total life-cycle duration of 22.9^0.58 days; fecundity (62.60^61.53 eggs per fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the present study, we found significant variations in the total developmental time, egg period and duration of the fourth instar. These are similar to the results obtained on cotton earlier (Bethke et al 1991;Thomas et al 2011). The developmental time from egg to adult of the 3 cryptic species ranged from 23.80 to 25.75 days when these were reared on cotton, which was longer than those reported for Asia II-1 from Pakistan (Ahmed et al 2014) and for B biotype (now referred as MEAM1) (Lida et al 2009) on different hosts, but nearly similar to the Cv biotype (now referred as Asia II-7) on cucumber and tomato (Qiu et al 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found significant variations in the total developmental time, egg period and duration of the fourth instar. These are similar to the results obtained on cotton earlier (Bethke et al 1991;Thomas et al 2011). The developmental time from egg to adult of the 3 cryptic species ranged from 23.80 to 25.75 days when these were reared on cotton, which was longer than those reported for Asia II-1 from Pakistan (Ahmed et al 2014) and for B biotype (now referred as MEAM1) (Lida et al 2009) on different hosts, but nearly similar to the Cv biotype (now referred as Asia II-7) on cucumber and tomato (Qiu et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies elaborate the biology, ecology and developmental characteristics of B. tabaci and its biotypes, i.e., B biotype (Perring 2001;Brown & Czosnek 2002;Jones 2003;Horowitz et al 2005;Liu et al 2007), Cv biotype (Qiu et al 2011), Q biotype (Drost et al 1998;Muniz & Nombella 2001) and Asia II-1 and MEAM 1 cryptic species (Ahmed et al 2014). Biological variations of B. tabaci had also been reported according to host plants, viz., cotton (Bethke et al 1991;Thomas et al 2011), sweet pepper (Muniz & Nombella 2001), eggplant and tomato (Tsai & Wang 1996), and soybean and garden bean (Mansaray & Sundufu 2009). But corroboration of life history traits with molecular data and genetic grouping had been largely inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Bemisia tabaci has a host range exceeding 600 plant species and is a major vector of numerous plant viruses which have a great impact on agriculture worldwide. Russell (1975) compiled literature on the biology and morphology of B. tabaci and other whitefl y species on legume crops, and numerous studies on the biology of B. tabaci under diverse environmental conditions have since been published (Butler et al 1983;Coudriet et al 1985Coudriet et al , 1986Mohanty & Basu, 1987;Bethke et al 1991;Powell & Bellow, 1992;Salas & Mendoza, 1995;Thompson, 2000;Musa & Ren, 2005;Fekrat & Shishehbor, 2007;Kumarasinghe et al 2009;Carabali et al 2010; Thomas et al 2011). Dialeurodes delhiensis, a forest pest which infests Ficus sp., was described from Delhi, and until now nothing has been known of its biology.…”
Section: Introductionmentioning
confidence: 99%